Sex in the Brain How Seizures, Strokes, Dementia, Tumors, and Trauma Can Change Your Sex Life - Baird, Amee (Columbia University Press, 2019)
What controls our sex lives? Our brains. Yet there is surprisingly little research into how our brains influence one of the most fundamental of all human behaviors. And there is even less understanding of what can happen to the sexuality of a person who suffers a brain injury or illness such as a stroke, Parkinson’s disease, or dementia.In Sex in the Brain, clinical neuropsychologist Amee Baird explores fascinating case studies of dramatic changes in sexual behavior and explains what these exceptional stories have to say about human sexuality. She illuminates the extraordinary insights into how the brain works that injury or disease can divulge. Each chapter includes striking personal accounts, many from individuals Baird has met in her clinical practice, of unexpected shifts in sexuality. Until now these fascinating, frightening, and funny stories have been hidden in medical journals or untold outside of the clinical setting. This revealing and sometimes heartbreaking book unfolds a better understanding of the links between brain function and our sexual selves